CENTRAL LABOR COUNCIL OF ALAMEDA CO; UNIONIST OF THE YEAR COMM - COLLINS,EJ (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Letter to A J Stevens, Lorillard, from E J Collins of the Central Labor Council of Alameda County. Invites Lorrilard to purchase and advertisment in the souvenir program of their annual "Unionist of the Year" dinner. Notes that council opposed Proposition 5.